Guidelines for implementing group counseling using a gestalt counseling approach to reduce student aggressivity - Zikry Latupasjana; Firman Firman (IICET (Indonesian Institute for Counseling, Education and Therapy), 2020)
Aggressiveness among adolescents in Vocational High Schools has increased significantly. Group counseling services in schools are rarely used to prevent drug abuse. Most group counseling is used to solve several problems, such as learning, personal, social, and career problems. This study aims to produce simple, valid, and effective guidelines for guidance and counseling teachers / counselors to reduce student aggressiveness. This research is a development (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The subjects of this study were students and supervisors at the Vocational High School in the city of Padang. The validity of this study was carried out by six experts associated with this study and the appearance of guidelines. The usability test was carried out by three supervisors. Data analysis is descriptive and inferential analysis with the Kendals coefficient statistical test. The results showed that: (1) The level of material suitability was very acceptable with a percentage of 93 percent and the appearance of the guidelines was also in the proper category with a percentage of 90.4 percent, (2) The use of group guidance guides using the gestalt counseling approach to reduce student aggressiveness was included in the category. The best with a percentage of 87. It can be concluded that this guideline is appropriate for use by supervisors / counselors as an effort to reduce student aggressiveness in vocational high schools in Padang city